Vitaliseringspsykologi i neurorehabilitering - Christensen, Lise (Psyke & Logos, 2015)
The article shows how a vitalising psychological approach can contribute to the area of neurorehabilitation for the purpose of understanding the psychological deficit position of the brain injured person. It is argued that a vitalising psychological understanding of the basic psychological needs in humans and their vitalising environments can contribute to the development of the holistic approach towards neurorehabilitation. Based on the premises in vitalising psychology, the discussion of the practical implications for this approach towards neurorehabilitation is contextualised within an integral framework that facilitates respect for complexity.